A STUDI ANALISIS SEMPADAN DAN GREENBELT TERHADAP KONDISI BENDUNGAN KEULILING - Bravikawati, Marini; Salsabila, Shafira (Program Studi Teknik Sipil, Fakultas Teknik. Universitas Samudra, 2025)
A dam is a structure designed to ensure the sustainable availability of water supply. One dam that plays a significant role in this regard is the Keuliling Dam, which makes a major contribution to meeting the water needs of the community. Despite offering numerous benefits, the existence of a dam also poses potential risks that must be properly anticipated. As part of mitigation efforts and maintenance planning, analysis of the buffer zone and greenbelt is essential at Keuliling Dam. This study employs a combination of primary and secondary data to support the evaluation process of the buffer zone and greenbelt conditions at the dam. The aim of this analysis is to assess each component based on observation results using a condition index approach. The assessment process begins with identifying damage in each subcomponent, followed by assigning scores according to the level of damage observed. Based on the analysis results, the condition index for the buffer zone and greenbelt is recorded at level 4, which indicates minor damage. This value reflects the current condition of these two components and serves as a critical reference for the planning and implementation of maintenance activities to ensure the dam's functionality is properly maintained. Keywords: dam, embankment, greenbelt